Pengaruh Hedging, Financial Lease dan Sales Growth terhadap Agresivitas Pajak - Winda Sangata Ramadhani; Dedik Nur Triyanto; Kurnia Kurnia (Journal of Applied Accounting and Taxation, 2020)
The purpose of this study was to determine the effect of hedging, financial lease, and sales growth on tax aggressiveness in mining companies listed on the Indonesia Stock Exchange in the 2011-2018 period. The total sample obtained from the reduction using the purposive sampling technique of 32 samples. The data analysis model used panel data regression analysis, descriptive statistical analysis, and classic assumption test. The results of this study are hedging, financial lease and sales growth have a simultaneous effect on tax aggressiveness. While partially hedging does not affect on tax aggressiveness, the financial lease has a positive effect on tax aggressiveness and sales growth has a negative affect on tax aggressiveness.